The role of the Economic Council in combating administrative and financial corruption (Journal of the College of Basic Education, 2022)
Corruption is the old and new topic that all people know and have heard a lot about, and this phenomenon has a different image, either administrative, financial, political, moral, social or natural, and what concerns us here is the administrative and financial corruption that our study is limited to.Administrative and financial corruption is represented in the misuse of public powers to achieve illegal private gains, or the use of power to practice illegal and immoral behavior, or the exploitation of public office for personal ends.The phenomenon of administrative and financial corruption is only the result of social and economic secretions resulting from scientific development, human lifestyle and transactions that extended across unspecified economic, political and geographical areas.